Mengurai Kesenjangan Partisipasi: Transparansi dan Dominasi Kelompok Tertentu dalam Perencanaan Pembangunan Desa Padang Brahrang - Ali, Chaidir; Ridwan, Mohammad (Jurnal Intervensi Sosial dan Pembangunan, 2025)
Village development planning based on community participation is essential for creating national welfare and stability. This study analyzes community participation in development planning in Padang Brahrang Village using the participatory village planning theory by Wicaksono and Sugiarto. A qualitative method was applied, with data collection techniques including observation, interviews, and documentation. A total of 8 informants were selected through purposive sampling, comprising village officials and community representatives. The research findings indicate: (1) community involvement is still dominated by specific groups, with participation limited to passive idea-sharing; (2) village government transparency is low, as critical information is only available in the Musrenbang (Development Planning Meeting) forum, restricting access for those who do not attend; and (3) gaps in participation and oversight of village development highlight the need for more inclusive and transparent participation mechanisms. Based on the findings, this study recommends: (a) new mechanisms to enhance community involvement, such as online surveys or digital platforms; (b) more inclusive village policies that involve vulnerable groups; (c) capacity building for village officials to conduct Musrenbang in a more participatory manner; and (d) equitable access to information through easily accessible media like village websites. These recommendations are expected to strengthen community participation and promote inclusive and sustainable village development.Keywords: Village Planning, Community Participation, Development, Transparency, Inclusivity.